The Exclusion of Ubuntu from South Africa's Constitution: Implications for Pan-Africanism and Violent 'Xenophobia' - Sesanti, Simphiwe (African studies (Johannesburg), 2025)
In 2023, the Organisation of African Unity (OAU), later renamed the African Union, turned 60. Premised on the philosophy of Pan-Africanism, the organisation was formed to unite Africans into a single nation in order to combat colonialism and establish a monolithic United States of Africa. The OAU's 60th anniversary coincided with the 30th anniversary of the adoption of South Africa's 1993 Interim Constitution, which included the philosophical concept 'ubuntu'. In the subsequent 1996 South African Constitution, however, ubuntu was excluded. In this article, I argue that the inclusion of ubuntu in the 1993 Interim Constitution offered Africans in South Africa an opportunity to raise their consciousness about the importance of self-re-humanisation after a period of violent colonial dehumanisation, and that the restoration of ubuntu to South Africa's Constitution could help in reconnecting South Africans to other Africans in the ongoing and elusive struggle for Pan-Africanism. This is especially the case amid South Africans' 'xenophobic' attacks against fellow Africans after South Africa became a democracy in 1994.